2018
DOI: 10.1016/j.ymthe.2018.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Mediated Small RNA Delivery: A Novel Therapeutic Approach for Inflammatory Lung Responses

Abstract: Exosomes (EXOs) are a type of extracellular nanovesicles released from living cells. Accumulating evidence suggests that EXOs are involved in the pathogenesis of human diseases, including lung conditions. In recent years, the potential of EXO-mediated drug delivery has gained increasing interest. In this report, we investigated whether inhaled EXOs serve as an efficient and practical delivery vehicle to activate or inhibit alveolar macrophages (AMs), subsequently modulating pulmonary immune responses. We first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 54 publications
(82 reference statements)
5
117
0
Order By: Relevance
“…These results suggest a role for miRNA in the anti‐inflammatory/regenerative function displayed by the CSSC EVs. Such a function is consistent with a number of recent studies that have linked miRNA delivery by EVs to regenerative, antifibrotic, and immune suppressive properties of the vesicles . Some authors have suggested that the small amount of miRNA in EVs makes it more likely that a protein cargo is involved in their biological properties .…”
Section: Discussionsupporting
confidence: 88%
“…These results suggest a role for miRNA in the anti‐inflammatory/regenerative function displayed by the CSSC EVs. Such a function is consistent with a number of recent studies that have linked miRNA delivery by EVs to regenerative, antifibrotic, and immune suppressive properties of the vesicles . Some authors have suggested that the small amount of miRNA in EVs makes it more likely that a protein cargo is involved in their biological properties .…”
Section: Discussionsupporting
confidence: 88%
“…Increasing data indicate that macrophages may create an optimal microenvironment for reducing inflammation through a paracrine mechanism [16][17][18], and exosomes secreted by macrophages play an important role in communicating with neighboring cells via regulating levels of cytokines and miRNAs to ameliorate the inflammatory response in recipient cells [19,20]. It has been reported that macrophage-derived exosomes attenuated thermal hyperalgesia in a murine model of inflammatory pain, suggesting their role in dysregulated inflammation [21].…”
Section: Introductionmentioning
confidence: 99%
“…EVs play important roles in cell-to-cell communications via cross-transferring of important signaling components [11][12][13][14] . For instance, EVs can carry and transmit mRNAs and miRNAs for promoting tumor growth, which has been identified as the diagnostic biomarkers for lung cancer 15 , breast cancer 16 and ovarian cancer 17,18 . The mRNAs found in smaller EVs (exosomes) can be transferred and translated to functional proteins after uptake by other cells 19 .…”
mentioning
confidence: 99%